Alternative splicing and its regulatory mechanisms in photosynthetic eukaryotes - Link, Alicia, author; Reddy, A. S. N., advisor; Stack, Stephen, committee member; Lapitan, Nora, committee member (Colorado State University. Libraries, 2011)
In recent years, alternative splicing (AS) of pre-mRNAs, which generates multiple transcripts from a single gene, has emerged as an important process in general proteome diversity and in regulatory gene expression in multicellular eukaryotes. In Arabidopsis over 40% of intron-containing genes are alternatively spliced. However, mechanisms by which AS is regulated in plants are not fully understood, primarily due to the lack of an in vitro splicing system derived from plants. Furthermore, the extent of AS in simple unicellular photosynthetic eukaryotes from which plants have evolved is also not known. My research addresses these two attributes of splicing in plants. In Part 1 of my thesis, I have investigated an aspect of AS regulation in plants. We have previously shown that an SR-related splicing regulator called SR45 regulates AS of pre-mRNAs in Arabidopsis by altering splice site selection (Ali et al. 2007). In this work using bimolecular fluorescent complements, I have demonstrated that SR45 interacts with U2AF35, an important spliceosomal protein involved in 3' splice site selection in plant cells. This interaction takes place in the nucleus, specifically in the subnuclear domains called speckles, which are known to contain splicing regulators and other proteins involved in transcription. My work has shown that SR45 interacts with both paralogs of U2AF35 and I mapped the domains in SR45 that are involved in its interaction with U2AF35. In addition, my studies have revealed interaction of the paralogs as hetero- and homodimers. Interestingly, U2AF35 was found to interact with U1-70K, a key protein involved in 5' splice site selection. Based on this work and previous work in our laboratory, a model is proposed that explains the role of SR45 in splice site selection. In the second part of my work I studied the extent of alternative splicing (AS) in the unicellular green alga Chlamydomonas, that shares a common ancestor with land plants. In collaboration with Dr. Asa Ben Hur's lab, we have performed a comprehensive analysis of AS in Chlamydomonas reinhardtii using both computational and experimental methods. Our results show that AS is common in Chlamydomonas, but its extent is less than what is observed in land plants. However, the relative frequency of different splicing events in Chlamydomonas is very similar to higher plants. We have found that a large number of genes undergo alternative splicing, and together with the simplicity of the system and the use of available molecular and genetic tools. This organism is an experimental system to investigate the mechanisms involved in alternative splicing. To further validate predicted splice variants, we performed extensive analysis of AS for two genes, which not only confirmed predictions but also revealed novel splice variants, suggesting that the extent of AS is higher than we predicted. AS can also play a role in the regulation of gene expression through processes such as regulated unproductive splicing and translation (RUST) that involves nonsense-mediated decay (NMD), a mechanism of mRNA surveillance that degrades transcripts containing premature termination codons (PTCs). The basic mechanism of NMD relies upon many factors, but there are three critical proteins, termed the UP-frameshift (UPF) proteins due to their ability to up-regulate suppression of nonsense transcripts. UPF1, UPF2, and UPF3 appear to be conserved across animals and plants. Our analysis of AS has found that in Chlamydomonas, many splice variants have a premature termination codon (PTC). However, to date, the mechanism of NMD has not been investigated in Chlamydomonas. Analysis of the Chlamydomonas genome sequence shows that UPF1, 2, and 3 proteins are present, and we have shown that they share some sequence similarity with both plants and humans, indicating that the process of NMD may be present in this organism. To address the role of UPFs in NMD in Chlamydomonas, we have utilized the artificial miRNA approach. I have generated stably transformed Chlamydomonas cell lines that are expressing amiRNA for UPF1 and UPF3 that will be useful in analyzing NMD of selected genes as well as all PTC-containing transcripts globally.
Keywords: algae; alternative splicing; NMD; SR45; U2AFs; Chlamydomonas